Polyproline–OEG Co‐Oligomeric Dendrimers: A Family of Highly Branched Polyproline Macromolecules. Issue 36 (5th November 2013) - Torres, Ángela; Albericio, Fernando; Royo, Miriam
Abstract: Here we describe a class of co‐oligomer polyproline–oligo(ethylene glycol) (OEG) dendrimers composed of multiple copies of a polyproline building block coupled around OEG‐ and proline‐based cores. We explored a new approach that allowed us to build, in a controlled way, highly branched dendrimers using only two reactions steps and very simple purification processes. This methodology yielded diverse highly branched OEG–peptide dendrimers with a high degree of purity without the use of multivalent chemical ligation processes or click chemistry. Abstract : A new family of co‐oligomer polyproline–oligo(ethylene glycol) (OEG) dendrimers were synthesized by coupling a polyproline building block to OEG‐ and proline‐based cores, using a new approach that allowed us to build one of the largest peptides (195 residues) ever synthesized by chemical methods without the use of multivalent chemical ligation processes or click chemistry.